Ionotropic Glutamate Receptors and Voltage-Gated Ca2+ Channels in Long-Term Potentiation of Spinal Dorsal Horn Synapses and Pain Hypersensitivity. (2nd October 2013) - Youn, Dong-ho; Gerber, Gábor; Sather, William A.
Abstract : Over the last twenty years of research on cellular mechanisms of pain hypersensitivity, long-term potentiation (LTP) of synaptic transmission in the spinal cord dorsal horn (DH) has emerged as an important contributor to pain pathology. Mechanisms that underlie LTP of spinal DH neurons include changes in the numbers, activity, and properties of ionotropic glutamate receptors (AMPA and NMDA receptors) and of voltage-gated Ca 2+ channels. Here, we review the roles and mechanisms of these channels in the induction and expression of spinal DH LTP, and we present this within the framework of the anatomical organization and synaptic circuitry of the spinal DH. Moreover, we compare synaptic plasticity in the spinal DH with classical LTP described for hippocampal synapses.